청소년 영양지수 (NQ-A 2021) 개정에 관한 연구 - 김기남(Ki Nam Kim); 황효정(Hyo-Jeong Hwang); 임영숙(Young-Suk Lim); 황지윤(Ji-Yun Hwang); 권세혁(Sehyug Kwon); 이정숙(Jung-Sug Lee); 김혜영(A)(Hye-Young Kim) (Journal of nutrition and health, 2023)
Purpose: This study was conducted to update the Nutrition Quotient for Adolescents (NQ-A), which is used to assess the overall dietary quality and food behavior among Korean adolescents. Methods: The first 30 candidate items of the measurable eating behavior checklist were obtained based on a previous NQ-A checklist, the results of the seventh Korea National Health and Nutrition Examination Survey data, Korea Youth Risk Behavior Survey data, national nutrition policies and dietary guidelines, and literature reviews. A total of 100 middle and high school students residing in Seoul and Gyeonggi Province participated in a pilot study using the 25-item checklist. Factor analysis and frequency analysis were conducted to determine if the checklist items were organized properly and whether the responses to each item were distributed adequately, respectively. As a result, 22 checklist items were selected for the nationwide survey, which was applied to 1,000 adolescent subjects with stratified sampling from 6 metropolitan cities. The construct validity of the updated NQ-A 2021 was assessed using confirmatory factor analysis. Results: Twenty checklist items were determined for the final NQ-A 2021. The items were composed of three factors: balance (8 items), moderation (9 items), and practice (3 items). The standardized path coefficients were used as the weights of items to determine the nutrition quotients. NQ-A 2021 and 3-factor scores were calculated according to the weights of questionnaire items. The weight for each of the 3 factors was determined as follows: balance, 0.15; moderation, 0.30; and practice, 0.55. Conclusion: The updated NQ-A 2021 is a useful instrument for easily and quickly evaluating the dietary qualities and eating behaviors of Korean adolescents. 본 연구의 청소년 영양지수 (NQ-A) 2021은 청소년의 식생활 및 식행동을 종합적, 객관적으로 평가할 수 있는 선별 영양진단 도구로 영양전문가 뿐만 아니라 청소년 스스로도 쉽게 이용할 수 있도록 하는 것을 목표로 제·개정이 수행되었다. 본 연구에서는 2015에 개발된 한국 청소년 영양지수 (NQ-A) 체크리스트 항목을 기반으로 국민건강영양조사 자료, 국가 영양정책 및 지침, 청소년의 영양상태와 식행동에 관한 문헌에 대한 검토와 전문가를 대상으로 한 심층면접을 진행하였고, 이를 통해 25개의 파일럿 조사용 체크리스트를 우선 선정하였다. 파일럿 조사는 청소년 100명을 대상으로 시행되었고, 탐색적 요인분석과 전문가 의견수렴 과정을 거쳐 22개의 전국 단위 조사용 체크리스트 항목을 도출하였다. 전국 단위 조사의 경우 6개 광역시를 기준으로 층화추출된 총 1,000명의 청소년을 대상으로 진행되었고, 탐색적 요인 분석을 통해 청소년 영양지수 평가항목을 균형, 절제, 실천의 3가지 요인으로 분류한 후 확인적 요인분석을 통해 구조방정식 모형에 적합한 최종 20개 문항으로 NQ-A 2021를 최종 확정하였다. 청소년 영양지수의 영역별 가중치는 각각 균형 0.15, 절제 0.30, 실천 0.55로 결정되었다. 최종 확정된 NQ-A 2021의 각 영역별 문항은 다음과 같다. 균형영역에는 채소, 과일, 우유나 유제품, 콩이나 콩제품, 생선이나 조개류, 달걀, 견과류, 전곡·잡곡류의 섭취빈도의 8개 문항이, 절제영역에는 라면, 단음식·단음료, 카페인 음료, 맵고 짠 찌개나 탕류, 기름진 간식·튀김류 섭취, 야식, 편의점 등 길거리 음식 섭취빈도와 스마트폰 등을 보면서 식사하기 및 과식빈도의 9개 문항이, 실천영역에는 아침식사 빈도와 식품표시 확인, 식사 전 손 씻기의 3개 문항이 포함되었다. 대면평가로 이루어진 전국단위 조사대상자의 NQ-A 2021 평균 점수는 51.49점이었고, 각 영역별 평균점수는 균형 41.39점, 절제 55.67점, 실천 52.96점으로 나타났다. 본 연구의 NQ-A 2021은 20개의 체크리스트를 통해 10분 내외의 시간으로도 청소년의 식행동과 식생활을 평가할 수 있고, 균형, 절제, 실천 영역별 구체적 등급을 확인할 수 있다는 점에서 활발하게 이용될 수 있다. 또한 NQ-A 2021은 대면 평가와 웹사이트를 통한 비대면 온라인 평가가 모두 가능하며, 결과의 해석과 활용 자료를 함께 제공함으로써 영양전문가를 통한 영양교육과 연구뿐만 아니라 청소년 스스로 자신의 영양관리에도 다양한 활용이 가능할 것으로 기대된다.